2018
DOI: 10.1177/1948550618766399
|View full text |Cite
|
Sign up to set email alerts
|

Changing Beliefs About Female Leader Advancement Following the 2016 U.S. Presidential Election

Abstract: Scholars have discussed the implications of positive leadership role models, including the impact of Barack Obama and Hillary Clinton’s political rise for aspiring leaders of underrepresented groups. However, there are also potential ramifications when those role models fail, shaping broader beliefs about the permeability of the glass ceiling. The current research tests this idea by evaluating the perceived promotability of male and female business leaders before ( n = 165) and following ( n = 159) the 2016 U.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Consistently across studies, a woman working in nontraditional job without success (job‐related or political) was rated as colder and less likable by social dominators, but as warmer and more likable by authoritarians. This analysis might be helpful to gain a better understanding of the reactions that women in leadership positions evoke, particular if they fail (see for example Yates & Okimoto, 2019, for research on the effect of Hillary Clinton's failed presidential bid on the perceived promotability of women as leaders).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently across studies, a woman working in nontraditional job without success (job‐related or political) was rated as colder and less likable by social dominators, but as warmer and more likable by authoritarians. This analysis might be helpful to gain a better understanding of the reactions that women in leadership positions evoke, particular if they fail (see for example Yates & Okimoto, 2019, for research on the effect of Hillary Clinton's failed presidential bid on the perceived promotability of women as leaders).…”
Section: Discussionmentioning
confidence: 99%
“…Past research has shown that success and failure of politicians can have downstream consequences on observers. Hence, following Barack Obama's successful presidential campaign levels of implicit prejudice have been found to be strongly reduced (Plant et al., 2009), whereas Hillary Clinton's nonsuccessful presidential bid elicited a reduction in the perceived promotability of women relative to men for leadership positions (Yates & Okimoto, 2019). Based on the findings of Studies 1a and 1b, we hypothesized that in particular liking for a woman with a nontraditional job background who is politically unsuccessful would be influenced in contrasting ways by RWA and SDO.…”
Section: Study 1bmentioning
confidence: 99%
“…Although research on stereotypes about gender and emotion suggests these stereotypes tend to remain stable over time (e.g., Shields et al, 2018), the sociohistorical context could also affect perceivers' judgments of anger appropriateness. Indeed, the COVID-19 pandemic that currently is sweeping the world is a reminder that historic and cultural events can have a broad effect on psychological phenomena (e.g., Plant et al, 2009;Sawyer and Gampa, 2018;Yates and Okimoto, 2019). Psychologists have been most engaged with investigating the direct effects of these events (e.g., Rudman et al, 2013).…”
Section: Influences Of Sociohistorical Contextmentioning
confidence: 99%